Prevalence and risk factors of work-related contact dermatitis symptoms among healthcare cleaners during the COVID-19 pandemic in Northwest Ethiopia: a multicentre cross-sectional survey. Issue 11 (29th November 2022) - Tesfaye, Amensisa Hailu; Engdaw, Garedew Tadege; Aragaw, Fantu Mamo; Kabito, Gebisa Guyasa
Abstract : Objective: This study was aimed to explore the prevalence and risk factors of work-related contact dermatitis (WRCD) symptoms among cleaners working in healthcare institutions in Gondar city, Northwest Ethiopia, during the COVID-19 pandemic. Design: A multicentre cross-sectional study was conducted from September to October 2021. An interviewer-administered standardised Nordic Occupational Skin Questionnaire, V.2002 (NOSQ-2002) was used to assess WRCD. The collected data were entered into EpiData V.4.6 and analysed using Stata V.14 software. The association between dependent and independent variables was computed with a binary logistic regression. The association was determined using an adjusted OR (AOR) with a 95% CI at a p value of <0.05. Setting: The study was conducted in Gondar city healthcare institutions, Northwestern Ethiopia. Participants: A total of 409 cleaners participated in this study. Outcome measures: The primary outcome is the prevalence of WRCD symptoms, which was measured using the NOSQ-2002. Results: The response rate was 95.6%. The majority, 302 (73.8%), of the study participants were female. The mean age (±SD) was 31 (±7.87) years old. The overall prevalence of self-reported WRCD during the last 12 months was 213 (52.1%) (95% CI (47.1% to 57.0%)). The highest symptoms reported were skin redness, 51.6% (n=110), and the most affected skin body sites were hands (hand dermatitis), 74.2% (n=158). Hand washing frequency more than 20 times per day (AOR=1.73, 95% CI (1.03 to 2.92)), personal history of eczema (AOR=1.46, 95% CI (1.01 to 2.42)) and lack of training on skin hazards (AOR=2.06, 95% CI (1.16 to 3.63)) were factors influencing the occurrence of WRCD. Conclusions: This study revealed the prevalence of WRCD is common during the COVID-19 pandemic. Adjusting hand washing frequency per day, educating people with atopy about the avoidance of exposure to skin irritants and providing training on skin hazards were recommended to minimise the condition.